Predictors of male circumcision incidence in a traditionally non-circumcising South African population-based cohort - Ortblad, Katrina; Bärnighausen, Till; Chimbindi, Natsayi; Masters, Samuel H.; Salomon, Joshua A.; Harling, Guy (PLOS ONE, 2018)
Background Voluntary medical male circumcision has been promoted in high HIV prevalence settings to prevent HIV acquisition in males. However, the uptake of circumcision in many sub-Saharan African settings remains low. While many studies have measured circumcision prevalence, understanding circumcision incidence and its predictors is vital to achieving ambitious circumcision prevalence targets. Setting Rural KwaZulu-Natal, South Africa. Methods We measured circumcision incidence over the period 2009-2014 in a longitudinal population-based cohort with high HIV prevalence and low circumcision prevalence. Multivariable survival models with Weibull distributions were used to assess socio-demographic, behavioral and biological predictors of circumcision incidence. Results Between 2009 and 2014, circumcision prevalence among males 15-49 years in the cohort increased from 3% to 24%. Among 6,203 males 15-49 years, 873 new circumcisions occurred over 13,678 person-years (incidence rate: 6.4/100 person-years, 95% CI 6.0-6.8). Circumcision incidence was substantially higher amongst young males: 15-19 year olds were twice as likely to circumcise as older males. In the survival model, shorter household distance to the nearest healthcare facility, knowledge of HIV status and biological HIV-negative status were associated with an increased likelihood of circumcision incidence. Conclusions Circumcision prevalence among males in rural KwaZulu-Natal remains well below South Africa’s national 80% coverage target across age groups. In this population, distance to the nearest healthcare facility and knowledge of HIV status were important independent predictors of circumcision incidence. Mobile circumcision clinics and innovative HIV testing services may be important tools to help achieve circumcision targets.